Rancang Bangun Aplikasi form online untuk pemesanan dan pengadaan barang internal pada Puskesmas Cogreg - Duta Agung Pramana; Farizi Ilham; Mohammad Hadi Purnomo; Zacky Nurfaqih Permana (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2026)
The rapid growth of information technology has driven healthcare institutions to modernize their data management and administrative workflows. Puskesmas Cogreg, a primary healthcare facility, still depends on manual procedures for internal goods ordering and procurement. This practice generates recurring operational problems: records remain disorganized, documents are prone to loss, and approval workflows frequently experience delays due to the lack of a centralized digital system. To resolve these issues, this study designs and builds a web-based online form application using the Waterfall method, which progresses sequentially through five stages: requirements analysis, system design, implementation, testing, and maintenance. The application equips medical staff with a digital request submission feature, enables warehouse heads to verify and approve requests, and provides real-time procurement status tracking for all authorized users. System validation used black-box testing across 24 functional scenarios, all returning results consistent with expected outputs. The application demonstrably improves procurement efficiency, reduces recording errors, accelerates approval decisions, and produces a more structured, transparent, and accountable administrative process at Puskesmas Cogreg.